Catalyst Recycling in the Suzuki Coupling Reaction: Toward a Greener Synthesis in the Pharmaceutical Industry - Shoma Mukai; Yusuke Yamada (Knowledge, 2022)
The Suzuki coupling is a transition metal-catalyzed, cross-coupling carbon–carbon (C–C) bond forming reaction between organic boron compounds and organic halides. As an operationally simple and versatilely applicable procedure, the Suzuki coupling reaction has found immense applications in drug discovery and development in the pharmaceutical industry. Recently, the topic of catalyst recycling has undergone intensive investigations with ever-growing interest in eco-friendly and sustainable synthesis. To recapitulate the latest progress in catalyst recycling in the Suzuki coupling reaction, this invited paper reviews key principles, benefits, challenges, and cutting-edge applications of recyclable catalysts for green synthesis of industrially valuable bioactive molecules. This review paper also discusses how artificial intelligence (AI) could further advance green synthesis of pharmaceutical products.